2005
DOI: 10.1021/jf040334y
|View full text |Cite
|
Sign up to set email alerts
|

Release of Nucleotides and Nucleosides during Yeast Autolysis:  Kinetics and Potential Impact on Flavor

Abstract: Nucleotides, particularly 5'-nucleotides, are important flavoring agents found in many foods and beverages. Their precise effect on the flavor of wines aged on lees has not been examined previously. In this study nucleotides and nucleosides released by yeast during autolysis in a model wine system and in Champagne wines were identified and quantified, and their impact on wine flavor was determined. Ribonucleotides only were detected in yeast autolysate and in Champagne wines. In wines ribonucleotides were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 26 publications
2
46
1
Order By: Relevance
“…Zhao and Fleet (2005) reported that RNA degradation plays a key role in yeast autolysis, this reaction leads to the release of 3 0 -, 5 0 -and 2 0 -ribonucleotides. Recently, Charpentier et al (2005), have recognised 5 0 -UMP, 5 0 -GMP and 5 0 -IMP in Champagne aged over lees. Even if these compounds are well recognised as flavour compounds, further studies are required to establish their impact on the sensorial properties of sparkling wines .…”
Section: Autolysis Compounds and Their Influence On Sparkling Wine Qumentioning
confidence: 99%
“…Zhao and Fleet (2005) reported that RNA degradation plays a key role in yeast autolysis, this reaction leads to the release of 3 0 -, 5 0 -and 2 0 -ribonucleotides. Recently, Charpentier et al (2005), have recognised 5 0 -UMP, 5 0 -GMP and 5 0 -IMP in Champagne aged over lees. Even if these compounds are well recognised as flavour compounds, further studies are required to establish their impact on the sensorial properties of sparkling wines .…”
Section: Autolysis Compounds and Their Influence On Sparkling Wine Qumentioning
confidence: 99%
“…It is characterized by the loss of membrane functionality and by the enzymatic degradation of nucleic acids, proteins, lipids and polysaccharides [16,17]. Most researches carried out on autolysis in oenology aimed at analyzing the products released into the medium [18][19][20][21], although morphological changes during autolysis have been studied in cells at the ultra structural level using microscopy techniques [22]. Moreover, in these studies only the determination of a single family of compounds was achieved using time consuming conventional chemical and biochemical techniques such as gas chromatography and high-performance liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, we induced autolysis in cells of Saccharomyces cerevisiae EC1118, a commercial wine yeast previously well characterized for its autolytic behaviour [18,19,21,22], both in a model wine medium and in a base wine. Measurements were carried out on yeast cells before and after 5 days of induced autolysis, when all major biochemical events are completed [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Limited evidence suggests that nucleotides could have an effect on wine taste (Charpentier et al, 2005). glutamic acid, Glu), nucleotides (e.g.…”
Section: Impact Of Yeast On Beer Tastementioning
confidence: 99%